Molecular divergence between Iridaea cordata (Turner) Bory de Saint-Vincent from the Antarctic Peninsula and the Magellan Region - Ocaranza-Barrera, Paula; Gonzalez-Wevar, Claudio A.; Guillemin, Marie-Laure; Rosenfeld, Sebastian; Mansilla Muñoz, Andres Omar (My University, 2019)
The distribution of the Southern Ocean (SO) biota is the result of major geological, oceanographic, and climate changes during the last 50 million years (Ma). Several groups of marine benthic organisms exhibit marked taxonomic similarities between the Antarctic Peninsula and southern South America, where families, genera, and even species are currently co-distributed in these continents. Several species of macroalgae including Gigartina skottsbergii, Plocamium cartilagineum, and Iridaea cordata are currently found on both sides of the Drake Passage. Advances in molecular techniques have allowed estimating phylogenetic relationships, levels of differentiation and divergence time estimates between populations from these continents in order to determine whether they constitute separate evolutionary units. In this study, we determine whether Iridaea cordata represents the same evolutionary unit in southern South America and the Antarctic Peninsula or if populations on the two sides of the Drake Passage represent different genetic lineages. According to our results, I. cordata populations from the Antarctic Peninsula and South America are clearly distinguishable evolutionary units with 8.31% and 3.17% mtDNA and cpDNA molecular divergence, respectively. The separation between Antarctic and South American populations of I. cordata occurred at the end of the Miocene, between 5 Ma (rbcL) and 9 Ma (COI-5P). These results are similar to those reported in G. skottsbergii on both sides of the Drake Passage. Thus, I. cordata populations on the two sides of the Drake Passage should be considered two sister species. Cryptic speciation plays an important role in the evolution of the Southern Ocean; thus, the systematics, biogeography, and biodiversity of the region require major revisions.
Keywords: southern ocean; rhodophyta; biogeography; antarctic circumpolar current; cryptic speciation; vicariance